In Situ Construction of Flexible VNi Redox Centers over Ni‐Based MOF Nanosheet Arrays for Electrochemical Water Oxidation. Issue 10 (5th September 2021) - Sun, Xuan; Zhang, Xiuxiu; Li, Yuanli; Xu, Yanzhi; Su, Hui; Che, Wei; He, Jingfu; Zhang, Hui; Liu, Meihuan; Zhou, Wanlin; Cheng, Weiren; Liu, Qinghua
Abstract: Atomic‐level design and construction of synergistic active centers are central to develop advanced oxygen electrocatalysts toward efficient energy conversion. Herein, an in situ construction strategy to introduce flexible redox sites of VNi centers onto Ni‐based metal–organic framework (MOF) nanosheet arrays (NiV‐MOF NAs) as a promising oxygen electrocatalyst is developed. The abundant redox VNi centers with flexible metal valence states of V +3/+4/+5 and Ni +3/+2 enable NiV‐MOF NAs excellent oxygen evolution reaction (OER) activity and a long‐term stability under high current densities, achieving current densities of 10 and 100 mA cm −2 at recorded overpotentials of 189 and 290 mV, respectively, and showing ignorable decay of initial activity at 100 mA cm −2 after 100 h OER operation. Operando synchrotron radiation Fourier transform infrared combined with quasi in situ X‐ray absorption fine structure spectroscopies reveal at atomic level that the flexible V sites can continuously accept electrons from adjacent active Ni sites to accelerate OER kinetics for NiV‐MOF NAs during the reaction process, accompanied by a self‐optimized structural distortion of VO6 octahedron for promoting the electrochemical stability. Abstract : NiV‐metal‐organic framework nanosheet arrays with flexible VNi redox centers are designed by an in situ construction strategy during the structural transformation of the Ni‐based double‐layer hydroxide precursor to concurrently boost the oxygen evolution reaction catalytic activity and maintain a robust long‐term durability under the high current density in alkaline media.